2006
DOI: 10.3354/meps308129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diatoms on copepod reproduction. I. Field and laboratory observations related to Calanus helgolandicus egg production

Abstract: Egg production rates (EPR) by Calanus helgolandicus females were investigated with specimens sampled weekly, from April to November 2003 and from March to October 2004, at a station located in the English Channel off Roscoff. Comparison of results between 1994Comparison of results between , 2003Comparison of results between and 2004 showed that C. helgolandicus was a late spawner in 1994 and became an early spawner in 2003 and 2004. In all cases high variations in EPR were observed, which could not be corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1

Year Published

2007
2007
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 45 publications
2
26
1
Order By: Relevance
“…The negative effect was weaker than starvation, but strong enough to make mixtures with adequate food supply of Rhodomonas and T. weissflogii inadequate. This contrasts with previous studies which used P. minimum as a control treatment against the negative impacts of diatoms as T. rotula on copepod hatching success (Chaudron et al 1996) and embryonic (Poulet et al 1994) as well as postembryonic development (Carotenuto et al 2002), and to reverse effects of diatom monodiets on copepod egg production (Poulet et al 2006). P. minimum Fig.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The negative effect was weaker than starvation, but strong enough to make mixtures with adequate food supply of Rhodomonas and T. weissflogii inadequate. This contrasts with previous studies which used P. minimum as a control treatment against the negative impacts of diatoms as T. rotula on copepod hatching success (Chaudron et al 1996) and embryonic (Poulet et al 1994) as well as postembryonic development (Carotenuto et al 2002), and to reverse effects of diatom monodiets on copepod egg production (Poulet et al 2006). P. minimum Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…Since the mid 1990s, there have been an increasing number of culture studies demonstrating a detrimental impact of diatoms on copepod larval development (Ianora et al 2004;Poulet et al 1994), including species of the genus Acartia . While some laboratory studies have shown that diatoms can also suppress egg production and hatching rates of copepods (Ianora et al 1995(Ianora et al , 2003, others show that copepod egg production can be increased or unaffected depending on the diatom species in the diet (Poulet et al 2006). Contrasting effects of diatom diet on copepods are reported from the field.…”
Section: Introductionmentioning
confidence: 87%
“…Meanwhile aldehydes and fatty acid hydroperoxides have been identified as the toxic compounds (Ianora et al 2004;Wichard et al 2005;Fontana et al 2007) and it has been shown that these compounds are produced by mechanical cell rupture (Pohnert 2000;Fontana et al 2007). The toxic effect has been identified as being particularly harmful to embryogenesis and thus to reduce the hatching success of eggs (Chaudron et al 1996;Poulet et al 2006). In other laboratory studies, no toxic effect was found, but under some environmental conditions, poor food quality, e.g.…”
Section: Discussionmentioning
confidence: 94%
“…This gradual decrease in hatching could still indicate a depletion or accumulation of other, bioactive or essential compounds controlling egg viability, but it might not necessarily be caused by a single factor. Hitherto unknown toxins might cause the failure of egg production or hatching on diatom diets, as recently suggested by Poulet et al (2006), but yet lack support from experimental studies and specific chemical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest an impaired reproduction of copepods associated with various diatom blooms in the field (Miralto et al 1999;Poulet et al 2006;Vargas et al 2006). Despite variable copepod egg production and egg hatching, however, no general negative relationship to diatom biomass has yet been established in various ecosystems (Laabir et al 1998;Irigoien et al 2002).…”
mentioning
confidence: 99%